Use of dispersion modelling for Environmental Impact Assessment of biological air pollution from composting: progress, problems and prospects - Douglas, Philippa; Hayes, Enda T.; Williams, Ben; Tyrrel, Sean F.; Kinnersley, Robert P.; Walsh, Kerry A.; O'Driscoll, Mella; Longhurst, Philip J.; Pollard, Simon J. T.; Drew, Gillian H. (Elsevier, 2017)
With the increase in composting as a sustainable waste management option, biological air pollution (bioaerosols) from composting facilities have become a cause of increasing concern due to their potential health impacts. Estimating community exposure to bioaerosols is problematic due to limitations in current monitoring methods. Atmospheric dispersion modelling can be used to estimate exposure concentrations, however several issues arise from the lack of appropriate bioaerosol data to use as inputs into models, and the complexity of the emission sources at composting facilities. This paper analyses current progress in using dispersion models for bioaerosols, examines the remaining problems and provides recommendations for future prospects in this area. A key finding is the urgent need for guidance for model users to ensure consistent bioaerosol modelling practices.
Keywords: Bioaerosols; Compost; Dispersion modelling; Environmental Impact Assessment